ฤทธิ์และกลไกการยับยั้งจุลินทรีย์ของไคโตซานตลอดจนอนุพันธ์ และคอมพอสิตของไคโตซาน - รักกะเปา, ณัฐธิดา; ไชยศรีขวัญ, บุญภพ; พัฒิยะ, อติพล; เพชรวัง, จรัสลักษณ์; วีระพันธ์, อุไรวรรณ (Science Essence Journal, 2017)
บทคัดย่อ ไคโตซาน เป็นพอลิเมอร์ธรรมชาติ มีความเข้ากันได้ทางชีวภาพกับเนื้อเยื่อสิ่งมีชีวิต และไม่เป็นพิษ ไคโตซานเป็นอนุพันธ์ของไคตินซึ่งพบเป็นองค์ประกอบในเปลือกแข็งของสัตว์ไม่มีกระดูกสันหลังจำพวก แมลง กุ้ง ปู หมึก และเป็นส่วนประกอบในผนังเซลล์ของ ยีสต์ รา และสาหร่าย ด้วยคุณสมบัติพิเศษของไคโตซานที่มีฤทธิ์ต้านการเจริญของเชื้อจุลินทรีย์ได้อย่างหลากหลาย ทั้งแบคทีเรียแกรมบวก แบคทีเรียแกรมลบ และราหลายชนิด ดังนั้นจึงมีการนำไคโตซานไปประยุกต์ใช้ในหลายด้านที่มีความเกี่ยวข้องกับการยับยั้งจุลินทรีย์ เช่น อุตสาหกรรมอาหาร อุตสาหกรรมสิ่งทอ การแพทย์ รวมถึงการเกษตร ดังนั้นความเข้าใจเกี่ยวกับกลไกการยับยั้งจุลินทรีย์ของไคโตซานจึงมีความจำเป็นอย่างยิ่งต่อการพัฒนาผลิตภัณฑ์และพัฒนากระบวนการนำไคโตซานไปใช้ประโยชน์ ดังนั้นบทความวิชาการนี้จึงได้รวบรวมข้อมูลทางวิชาการต่างๆ ที่เกี่ยวข้องกับฤทธิ์และกลไกการยับยั้งจุลินทรีย์ ตลอดจนการประยุกต์ใช้ไคโตซาน อนุพันธ์และคอมพอสิตของไคโตซาน รวมถึงการใช้ไคโตซานร่วมกับสารตัวเติมอื่นเพื่อเสริมฤทธิ์ยับยั้งจุลินทรีย์ไว้อย่างครบถ้วน - - - Anti-Microbial Activity and Mechanisms of Chitosan along withChitosan Based Derivatives and Composites ABSTRACT Chitosan is a natural, biocompatible, and nontoxic polymer. It is a derivative of chitin, obtained from the hard outer shell or exoskeleton of invertebrates, including insects, shrimp, crab, squid, as well as from the cell walls of yeasts, molds and algae. Because of its anti-microbial properties against gram-positive and gram-negative bacteria as well as fungi, chitosan could have many anti-microorganism applications in fields such as food and textile industries, agriculture and medicine. Thus, understanding the antimicrobial mechanisms of chitosan is very important to the development of products and processes for such chitosan applications. In that context, this review summarizes the technical information available on anti-microbial activities and their mechanisms; and the current applications of chitosan or its derivatives, singly or in composites; and the synergistically antimicrobial combinations of chitosan and other fillers.